Development of Crosslinked Bone Extracellular Matrix Hydrogels Using Naturally Derived Reagents - Jones, J.N. (2024)
Biomaterials developed from tissue derived extracellular matrices (ECM) have become increasingly popular in regenerative medicine, with the bioinstructive properties of ECM facilitating constructive remodelling following injury. An ECM derived hydrogel is currently undergoing clinical trial as an injectable therapy; however, the relative fragility of hydrogels could limit utility in areas where site retention or mechanical load bearing are of a concern. Current ECM products utilise exogenous reactive agents, such as glutaraldehyde (GA), to induce crosslinking within the collagenous network of the ECM, increasing material strength. However, concerns over glutaraldehyde cytotoxicity and implant calcification have led investigation into naturally derived crosslinking agents, including genipin (GP) and proanthocyanidins (PA). This thesis explores the potential impacts of GP and PA crosslinking on bone derived ECM hydrogels. By increasing intermolecular crosslinks within the gel structure, GP and PA may alter the mechanical and physical properties of the ECM hydrogel, whilst maintaining biocompatibility. Using a crosslinking methodology developed within this study, these properties were compared against those achieved by GA crosslinking. Crosslinking with PA resulted in significant increases to gel strength in comparison to GA crosslinking. Treatment with GP resulted in significantly increased mechanical strength in comparison to non-crosslinked gels but was lower than impacts from GA crosslinking. Use of PA significantly increased the strength of bone ECM hydrogels, conferring resistance to enzymatic degradation, however this was not achieved through GP treatment. The observed effects of PA were not bone ECM dependent, also significantly increasing the mechanical strength of small intestine and liver ECM hydrogels. In vitro examination of the crosslinked bone ECM hydrogels demonstrated increased biocompatibility following GP crosslinking, however PA treatment caused a severe cytotoxic response in cells (SH-SY5Y neuroblastoma cells). Despite this, differences in cytotoxic response were observed upon testing of a different cell line (L929 fibroblasts). The comprehensive study of mechanical, physical, biochemical and biocompatible impacts within this thesis has increased understanding of how genipin and proanthocyanidins impact bone derived ECM hydrogels. Crosslinker, concentration, time, ECM source and material form all affect the interaction between GP/PA and ECM, and its subsequent biocompatibility. Controlling these interactions may facilitate generation of ECM hydrogel constructs with increased functionality and increase future clinical utility.